2009
DOI: 10.1016/j.cogpsych.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Vowel categorization during word recognition in bilingual toddlers

Abstract: Toddlers’ and preschoolers’ knowledge of the phonological forms of words was tested in Spanish-learning, Catalan-learning, and bilingual children. These populations are of particular interest because of differences in the Spanish and Catalan vowel systems: Catalan has two vowels in a phonetic region where Spanish has only one. The proximity of the Spanish vowel to the Catalan ones might pose special learning problems. Children were shown picture pairs; the target picture’s name was spoken correctly, or a vowel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 83 publications
(135 reference statements)
2
108
0
Order By: Relevance
“…Their results suggest that, unless children experience a high proportion of Catalan input, they are indifferent to words mispronounced with the Catalan /e/ -/E/ vowel difference-again, consistent either with merging representations or understanding the representations' equivalence. Ramon-Casas et al (2009), as well as Albareda-Castellot, Pons, and Sebastián-Gallés (2011), suggest that indifference to Catalan vowel changes in word recognition may be driven by the relatively high cognate overlap between Catalan and Spanish. These cognates largely differ in their vowels, which, the argument goes, leads children to attend less to subtle differences in vowel sounds (see RamonCasas & Bosch, 2010, for evidence that Catalan vowels are preserved in noncognate words).…”
Section: Learning New Words In Multiple Accentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results suggest that, unless children experience a high proportion of Catalan input, they are indifferent to words mispronounced with the Catalan /e/ -/E/ vowel difference-again, consistent either with merging representations or understanding the representations' equivalence. Ramon-Casas et al (2009), as well as Albareda-Castellot, Pons, and Sebastián-Gallés (2011), suggest that indifference to Catalan vowel changes in word recognition may be driven by the relatively high cognate overlap between Catalan and Spanish. These cognates largely differ in their vowels, which, the argument goes, leads children to attend less to subtle differences in vowel sounds (see RamonCasas & Bosch, 2010, for evidence that Catalan vowels are preserved in noncognate words).…”
Section: Learning New Words In Multiple Accentsmentioning
confidence: 99%
“…This implies that those infants either did not distinguish differences between the two variants or understood their Downloaded by [Sarah Creel] at 21:52 07 November 2013 equivalence (interestingly, Sundara, Polka, & Molnar, 2008, show that younger French-English bilingual infants can distinguish sounds between languages). Ramon-Casas et al (2009), in a looking-while-listening paradigm, found that bilingual toddlers' recognition of mispronounced Catalan words was not impaired when the mispronunciation involved a vowel pair only present in Catalan (/e/ vs. /E/). Among preschoolers, only Catalan-dominant (but not Spanish-dominant) bilingual children's word recognition was impaired by such mispronunciations.…”
Section: Learning New Words In Multiple Accentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Ramon-Casas et al (2009) showed that word recognition is specific to phonetic contrasts that have phonemic status in the native language. When tested on mispronunciations that involve a vowel distinction that is used in Catalan but not in Spanish (/e/ -/E/), Catalan 18-month-olds showed an advantage for the correctly pronounced words over the mispronunciations, while Spanishlearning infants responded identically to both correct and mispronounced versions.…”
Section: Same Trialmentioning
confidence: 99%
“…The phonological specification of vowels in the initial lexicon has also been explored in children from 12 months onwards, using the same methodological approach (Mani and Plukett, 2007;Mani, Coleman and Plunkett, 2008;Mani and Plukett, 2010;Ramon-Casas, Swingley, Sebastián-Gallés and Bosch, 2009). The findings of these studies suggest that children are sensitive to changes in the quality of the vowels represented in their first words and respond differently when mispronunciations are created via a vowel change that is contrastive in the native language (Ramon-Casas et al, 2009).…”
Section: Mani and Plunkett 2010mentioning
confidence: 99%